DESIMINASI TEKNOLOGI SEDERHANA PADA PETANI KOPI UNTUK PENINGKATAN DAN PENGEMBANGAN MUTU OLAHAN BIJI KOPI - Rian Ade Pratama; Chusnul Chotimah; Junita Waryati; Gizka Desinta Pratiwi (Universitas Pattimura, 2026)
This Community Service Program (PKM) was implemented to address the problems faced by coffee farmer groups in Kamno Sari Village, Jagebob District, Merauke Regency. The area has considerable potential for coffee production; however, it has not been optimally managed due to limited knowledge, processing technology, and marketing systems. Field identification revealed three main problems: low farmer skills in coffee bean processing, production processes that remain traditional and do not meet quality standards, and limited processing facilities and infrastructure, which reduce product competitiveness. In addition, coffee marketing is still confined to the local area and has not yet maximized the use of digital technology. Based on these conditions, this PKM program aimed to disseminate appropriate and easily applicable technologies for farmers, including post-harvest handling techniques, the use of simple but effective processing equipment, and digital packaging and marketing strategies based on social media. The program was implemented using a participatory approach through training activities, equipment demonstrations, and intensive assistance to farmer groups. All members of the farmer group participated actively, and the activities were carried out smoothly according to the planned schedule. The farmers showed particularly high engagement during the simulation of appropriate technology using a coffee bean huller machine. The coffee huller machine provided to the partner group served as a practical tool for post-harvest coffee bean processing. The results of the community service activities indicate an increase in farmers’ knowledge and skills in improving coffee quality. The availability of adequate and functional production facilities also supported higher productivity and improved post-harvest outcomes for the farmer group.